Evaluation of abrasive wear behavior of dual ceramic whisker reinforced epoxy composites. (October 2016) - M., Sudheer
Graphical abstract: Highlights: First study to evaluate the effect of potassium titanate whiskers on abrasive wear of epoxy. Friction is a complex phenomenon and wear performance dependent greatly on grit size. Discussion on worn surface using SEM. Abstract: Two body abrasive wear behavior of potassium titanate whisker reinforced epoxy composites was studied at different loads, sliding distances and abrasive grit sizes and compared with epoxy matrix. The pin-on-disc study demonstrated that addition of whiskers was beneficial in improving abrasive wear performance of epoxy when worn against fine sized abrasives. The opposite effect was observed when rubbed against medium and coarse sized abrasives. Coefficient of friction was found to vary in a complex manner with whisker addition and sliding conditions. Scanning electron microscopy revealed that micro-ploughing and micro-scale fragmentation of whisker and the matrix are dominant abrasive wear mechanisms.